THE USE OF PEER EDITING TO IMPROVE STUDENTS’ WRITING SKILL - Intan Puspita Sari; Giantina Fajar Wati (IKIP Siliwangi, 2019)
This research aimed at improving students’ skills of writing for the eleventh grade students of SMK TI Pembangunan Cimahi through the use of peer editing. It is expected that peer editing can be used to improve the students’ writing skill in recount text in SMK TI Pembangunan Cimahi. This research was an action research study that consisted of two cycles. In doing the research, the researcher involved 33 students of Class XI as the respondent of the research. The data was collected by observation and writing test. The result of this research indicated that peer editing improve student writing skill from cycle to cyle. It means peer editing technique can improve students writing skill.The researcher also found that peer editing was appropriate technique for students grade XI in SMK TI Pembangunan Cimahi. Beside of learning writing it self, by using this technique student also learnt how to be cooperative in pair, because peer editing was done by pairing. The students’ writing ability in recount text improved in two cycles from 52 in cycle 1 then improved to 72 in cycle 2. The improvements of this study were particularly in students’ writing on generic structure and language features of recount text.Keywords: peer editing, writing, vocational high school